Indonesian Autonomous EFL Learners’ Perceptions On Writing Fiction In X Application - Raudhotul Nisfaa Hidayatullah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aimed to explore Indonesian autonomous EFL learners’ perceptions of writing fiction on X Application in relation to the development of their English writing ability. Employing a qualitative case study design, this research involved two Indonesian university students who actively wrote English fiction on X Application and were selected using purposive sampling. Data were collected through semi-structured interviews and analyzed using deductive thematic analysis based on Robbins and Judge’s (2017) Perception Theory, which consists of the perceiver, target, and situation components. The findings revealed that the participants perceived writing fiction on X Application as a meaningful activity that supported the development of their English writing ability. Positive attitudes, intrinsic motivation, prior English learning experiences, and personal interests encouraged them to write consistently, while the platform’s features, such as threaded storytelling, immediate feedback, and interaction with readers, enhanced their creativity, vocabulary, grammatical awareness, narrative organization, and confidence in writing. Furthermore, flexible writing conditions and engagement with the online writing community strengthened their autonomous learning process. Overall, the study concludes that X Application serves not only as a social networking platform but also as an effective medium for autonomous English language learning and creative writing practice among Indonesian EFL learners.
Finalisasi 23 Juli 2026_Yudi
Keywords: Autonomous Learning; EFL Learners; Perception; Writing Ability; X Application